CFD study on thermal transport in open-cell metal foams with and without a washcoat: Effective thermal conductivity and gas-solid interfacial heat transfer. (6th April 2017) - Peng, Wenping; Xu, Min; Li, Xunfeng; Huai, Xiulan; Liu, Zhigang; Wang, Huasheng
Highlights: The influence of washcoat on effective thermal conductivity of metal foams was analyzed. A correlation of effective thermal conductivity for coated metal foams was proposed. The flow and gas-solid heat transfer characteristics of coated metal foams were obtained. The viscous flow in washcoat enhances gas-solid interfacial heat transfer. Abstract: Metal foams are considered to be attractive catalyst carriers for strongly exothermic/endothermic catalytic processes, but the washcoat may have a significant influence on the thermal transport properties of the metal foams. In this work, the effective thermal conductivity and the gas-solid interfacial heat transfer of coated metal foams were studied using a periodic unit cell model in the CFD method. We emphasized analysing the effect of the washcoat on the effective thermal conductivity, pressure drop and interfacial heat transfer of metal foams. The results indicated that the influence of the washcoat on the effective thermal conductivity depends on the conductivity in three phases. A large deviation was found when we used the available empirical correlations for metal foams to predict the effective thermal conductivity of the coated metal foams. A correlation for the effective thermal conductivity of coated metal foams was proposed by considering the washcoat as a separate phase. With increasing washcoat thickness, it was found that the pressure drop increases but the gas-solid interfacial heat transfer decreases. Moreover, we verified the enhancement of viscous flow within the washcoat for coated metal foams. It was revealed that a maximum increase of the Nusselt number by a factor of approximately 13 was obtainable in turbulent flow if the viscous flow within the washcoat was accounted for. The present study may provide a guide for structured catalyst and reactor design for strongly exothermic/endothermic catalytic processes.